2012
DOI: 10.1029/2011jc007513
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in Arctic Ocean circulation revealed by iodine‐129 observations and modeling

Abstract: Anthropogenic radionuclides released into European coastal waters from nuclear fuel reprocessing plants at Sellafield (UK) and La Hague (France) flow northward through the Nordic Seas and label Atlantic Water (AW) entering the Arctic Ocean. Transport of the soluble radionuclide 129I through the Arctic Ocean has been simulated using a numerical model for the period from 1970 to 2010. The simulated tracer distributions closely conform to 129I measurements made across the Arctic Ocean during the mid‐1990s and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
124
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 66 publications
(128 reference statements)
12
124
1
1
Order By: Relevance
“…While the Atlantic Water in the Fram Strait has warmed since 1997, showed that there is a strong seasonal cycle in the Atlantic Water transport through the Fram Strait, but that there is no statistically significant interannual trend between 1997 and 2010 in the volume transport. We consider the longterm average volume flux of the following water masses: Atlantic Water advected in the WSC, defined as longitude ≥ 5 • E and depth ≤ 840 m; Polar Water flowing southward in the EGC, defined as mean temperature ≤ 1 • C and depth ≤ 400 m; and Recirculating and Arctic Atlantic Water which is both due to the recirculation of Atlantic Water in the Fram Strait (de Steur et al, 2014) and the long loop of Atlantic Water through the Arctic Ocean (Karcher et al, 2012), defined as longitude ≤ 1 • E and depth ≤ 840 m, and not as Polar Water. The estimate of the volume transport across the Fram Strait below 840 m from the moorings is more complicated.…”
mentioning
confidence: 99%
“…While the Atlantic Water in the Fram Strait has warmed since 1997, showed that there is a strong seasonal cycle in the Atlantic Water transport through the Fram Strait, but that there is no statistically significant interannual trend between 1997 and 2010 in the volume transport. We consider the longterm average volume flux of the following water masses: Atlantic Water advected in the WSC, defined as longitude ≥ 5 • E and depth ≤ 840 m; Polar Water flowing southward in the EGC, defined as mean temperature ≤ 1 • C and depth ≤ 400 m; and Recirculating and Arctic Atlantic Water which is both due to the recirculation of Atlantic Water in the Fram Strait (de Steur et al, 2014) and the long loop of Atlantic Water through the Arctic Ocean (Karcher et al, 2012), defined as longitude ≤ 1 • E and depth ≤ 840 m, and not as Polar Water. The estimate of the volume transport across the Fram Strait below 840 m from the moorings is more complicated.…”
mentioning
confidence: 99%
“…The cooling trend in the central Canada Basin and the warming trend along its southern perimeter are a consequence of deepening of the warm Atlantic water in the central basin and concurrent upwelling of warm Atlantic water at the boundaries, a manifestation of an intensification of the anticyclonic Beaufort Gyre in recent years (e.g., McLaughlin et al, 2009;Karcher et al, 2012;Zhong and Zhao, 2014). Although similar trends can be found in other seasons (from winter to spring), they are not statistically significant.…”
Section: Temporal Trendmentioning
confidence: 69%
“…The effect of remote forcing is another important issue to be examined. Advection of anomalous water masses introduces scales governed by mechanisms outside of the basin and/or shelf-basin interaction, such as the inflow of anomalous Pacific water into the deep basin (Steele et al, 2004;Itoh et al, 2012), its modification processes on the shelf (Pickart et al, 2005, Woodgate et al, 2005, the advection of anomalous Atlantic water Karcher et al, 2012), or variations of freshwater supply due to river runoff (Lammers et al, 2001). In this study, we employed level surfaces, as we focus on the applicability of the decorrelation scales for model validation and data assimilation (many models use the so called z-coordinate system).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of remote forcing is another important issue to be examined. Advection of anomalous water masses introduce scales governed by mechanisms outside of the basin and/or shelf-basin interaction, such as the inflow of anomalous Pacific Water into the deep basin [ Steele et al, 2004;Itoh et al, 2012], its modification processes on the shelf [Pickart et al, 2005, Woodgate et al, 2005, the advection of anomalous Atlantic Water Karcher et al, 2012], or variations of freshwater supply due to river runoff [Lammers et al, 2001]. In this study we employed level surfaces, as we focus on the applicability of the decorrelation scales for model validation and data assimilation (many models use the so called z-coordinate system).…”
Section: Resultsmentioning
confidence: 99%
“…The cooling trend in the central Canada basin and the warming trend along its southern perimeter is a consequence of deepening of the warm Atlantic Water in the central basin and concurrent upwelling of warm Atlantic Water at the boundaries, a manifestation of an intensification of the anticyclonic Beaufort Gyre in recent years [e.g., McLaughlin et al, 2009;Karcher et al, 2012;Zhong and Zhao, 2014]. Note The temporal trend in each location is used to define a time-varying background field.…”
Section: Temporal Trendmentioning
confidence: 99%